The love haters : a novel [compact disc, unabridged] - Center, Katherine (Macmillan Audio, 2025)
Producer Janie Vaughn's co-worker helps her get a career-making gig profiling a Coast Guard rescue swimmer (who just happens to be his brother), by claiming, falsely, that Janie is his girlfriend. As Janie spends time in Key West with the swimmer, Tom "Hutch" Hutcheson (along with his colorful Aunt Rue and his rescue Great Dane), she gets trapped by that lie, falling madly for Hutch, even as he thinks she's the one woman on earth he can't date. Swim lessons, helicopter flights, conga lines, drinking contests, hurricanes, and stolen kisses ensue, along with chances to tell the truth, to face old fears, and to be truly brave at last.